Phosphate desorption from soil in anion-exchange resin extraction - Aura, Erkki (Agricultural and Food Science, 1978)
An attempt was made to clarify the mechanisms of phosphate desorption using the anion exchange resin method for extraction of phosphorus from soil. It was shown that there is a linear dependence between the amount of phosphorus desorbed and the square root of the desorption time. Through theoretical examination it was concluded that the above-mentioned relation between the desorption and time is a result of the diffusion of phosphate from porous soil medium. Using this interpretation of the desorption curve as a basis, the activation energy of the phosphate desorption was calculated from the experimental results obtained with resin extraction at different temperatures. The activation energy values were 32—64 kJ/mol depending on soils involved. In application of the results, the mechanisms and rate at different steps of the desorption were examined.